Groundwater quantity and quality management - Aral, M. M.; Taylor, Stewart W. (American Society of Civil Engineers, 2011)
Sponsored by the Groundwater Hydrology Technical Committee of the Groundwater Council of the Environmental and Water Resources Institute of ASCE. Groundwater Quantity and Quality Management presents the best of current thinking on managing groundwater resources, focusing on the interrelationship between quantity and quality. Groundwater is an essential resource, yet it is subject to overuse and contamination both in the United States and abroad. Effective management of groundwater is imperative to ensure continued access to clean, accessible, and plentiful water supplies. This volume presents state-of-the-art essays on modeling groundwater flow and solute transport for purposes of forecasting; developing groundwater resources with consideration of groundwater-surface water interaction and saltwater intrusion; and remediating groundwater resources by physical, chemical, and biological means. This report is of immediate relevance to environmental engineers, hydrogeologists, water resources managers and regulators, and municipal officials responsible for maintaining water supplies through the management of groundwater.
"Sponsored by Groundwater Management Technical Committee of the Groundwater Council of EWRI, Environmental and Water Resources Institute (EWRI) of the American Society of Civil Engineers."
Keywords: Groundwater -- Management.; Groundwater -- Quality.; elektronické knihy; electronic books